Self and Knowledge - M. A. Muqtedar Khan (International Institute of Islamic Thought, 1999)
The contempomy intellectual revival of Muslim societies proposes a profound but problematic relationship between identity and epistemology, and between self and knowledge. I propose to elucidate this relationship and its implications by making a fundamental distinction between self and identity, and showing how there can be many identities but only one self. I begin by inquiring into the meaning of identity symbols such as “Islam” or “Muslim” prior to knowledge. For example, what is the meaning and relationship between identity and knowledge in Islamization of knowledge or Islamic Philosophy? In both types of knowledge, identity is prior to knowledge in an epistemological, as well as an ontological sense. Ontologically we are suggesting that the existence of Islamic psychology or Islamic philosophy is contingent on the being of an agency such as Islam or Muslims. Epistemologically we are arguing that Islam includes a theory of knowledge, and Islamic principles constitute paradigmatic values from which Islamic psychology or Islamic philosophy can be derived. Cleqly, the prefix Islamic gives an identity to knowledge. In other words, there are certain truth claims which derive their legitimacy not because their truth is self-evident or rationally deducible or empirically verifiable, but because they satisfy certain criteria which establishes their identity as Islamic. The issue of criteria that determine what constitutes knowledge (epistemology) is indeed crucial. The first thing that needs to be resolved is whether these criteria are universally intelligible or are functions of culturehdentity and value systems. I would like to posit that in the realms of socially meaningful practices it is possible to have relativistic criteria for determining the validity of social truths. Knowledge about answers to questions such as Is polygyny or homosexuality acceptable? or Are religious rights more important than economic rights? may be determined based on criteria that are located within the corpus of tradition and ethos of a given cultural milieu This is accomodation of cultural p l d s m . But in the realms of science and philosophy, reasoning and empirical evidence alone ...